Rapid changes in synaptic vesicle cytochemistry after depolarization of cultured cholinergic sympathetic neurons (The Rockefeller University Press, 1985)
Sympathetic neurons taken from rat superior cervical ganglia and grown in culture acquire cholinergic function under certain conditions. These cholinergic sympathetic neurons, however, retain a number of adrenergic properties, including the enzymes involved in the synthesis of norepinephrine (NE) and the storage of measurable amounts of NE. These neurons also retain a high affinity uptake system for NE; despite this, the majority of the synaptic vesicles remain clear even after incubation in catecholamines. The present study shows, however, that if these neurons are depolarized before incubation in catecholamine, the synaptic vesicles acquire dense cores indicative of amine storage. These manipulations are successful when cholinergic function is induced with either a medium that contains human placental serum and embryo extract or with heart-conditioned medium, and when the catecholamine is either NE or 5-hydroxydopamine. In some experiments, neurons are grown at low densities and shown to have cholinergic function by electrophysiological criteria. After incubation in NE, only 6% of the synaptic vesicles have dense cores. In contrast, similar neurons depolarized (80 mM K+) before incubation in catecholamine contain 82% dense-cored vesicles. These results are confirmed in network cultures where the percentage of dense-cored vesicles is increased 2.5 to 6.5 times by depolarizing the neurons before incubation with catecholamine. In both single neurons and in network cultures, the vesicle reloading is inhibited by reducing vesicle release during depolarization with an increased Mg++/Ca++ ratio or by blocking NE uptake either at the plasma membrane (desipramine) or at the vesicle membrane (reserpine). In addition, choline appears to play a competitive role because its presence during incubation in NE or after reloading results in decreased numbers of dense-cored vesicles. We conclude that the depolarization step preceding catecholamine incubation acts to empty the vesicles of acetylcholine, thus allowing them to reload with catecholamine. These data also suggest that the same vesicles may contain both neurotransmitters simultaneously.